The Fraud Pentagon Theory Perspective: Fraudulent Financial Reporting In Sharia Banking Registered At Financial Service Authority (OJK) - Agus Sulaeman; Nunung Nurhasanah; Rina Maria Hendriyani (Faculty of Islamic Business and Management, 2025)
ABSTRACT AGUS SULAEMAN, Fraud Pentagon Theory Perspective: Fraudulent Financial Reporting in Sharia Banking registered at Financial Services Authority (OJK), Magister Managemen Study Programs, College of Singaperbangsa University karawang, 2025. This research aims to examine the effect of fraud pentagon theory towards Fraudulent Financial Reporting in Sharia Banking registered at Financial Services Authority (OJK). Fraud pentagon theory includes five elements, namely Pressure proxied by financial target, financial stability, external pressure, and institutional ownership, Opportunity proxied by ineffective monitoring, and quality of external auditor, Rationalization proxied by change in auditor, Capability proxied by change in directors, and Arrogancy proxied by frequent number of CEO’s picture. This type of research is quantitative research. Samples were taken by using purposive sampling and data analysis tool used is SPSS (Statistical Package for the Social Sciences). The results of this research stated that financial target, financial stability, external pressure, institutional ownership, ineffective monitoring, change in auditor, and change in director does not affect Fraudulent Financial Reporting. While quality of external auditor and frequent of CEO’s picture has a positive significant effect on Fraudulent Financial Reporting. So its proves that Sharia Banking must carry out financial statement audits and prioritize the quality of external auditor to prevent fraudulent financial reporting. Keywords: Fraud, Fraud Pentagon Theory, Fraudulent Financial Reporting, Sharia Bank